(untitled) (Research, Society and Development, 2021)
In this work, the chemical composition of the artificial almond flavoring was investigated, as well as the toxicity of this additive against bioassays commonly used to assess the environmental risk offered by chemical compounds and/or substances. The chemical identification detected ethanol (solvent), saccharin, benzaldehyde and benzoic acid. In L. sativa and A. cepa, concentrations of 100 and 10 µL/L flavoring caused a reduction in the germination rate and inhibition of root growth. In A. cepa, at 24 and 48 hours of exposure, concentrations 100 and 10µL/L significantly reduced the division of root meristems, and concentrations 1 and 0.10 µL/L induced cellular changes and were aneugenic to plant meristems. The flavoring was highly toxic to A. salina with LC50 = 0.082 ppm. Also, by partitioning into saturated solutions of octane and water, the commercial solution of the almond presented a log Kow of 1.37. Based on the results obtained, under the established analysis conditions, the flavoring was significantly phytotoxic, cytogenotoxic and toxic, and based on Kow it is estimated to have good stability in water and soil. These results indicate that almond flavoring is a potential environmentally toxic compound.